ANALISA UMUR PAKAI (LIFETIME) BALL BEARING TIPE UCF 4 BOLT FLANGE UNIT PADA MESIN SPIN COATING ABRASIVE CLUTCH TEST DI PT XY - Syaiful Azis; M Zakinura (Jurnal Poli-Teknologi, 2017)
ABSTRACTSpin Coating Abrasive Clutch Test Machine is a machine for testing abrasive clucth on clutch components of PT.XY four-wheeled clutch. One component that plays an important role in the Spin Coating Abrasive Clutch Test Machine is a type bearing Ball Bearing type UCF 4 Bolt Flange Unit. Problems with the bearings may interfere with the performance and results of abrasive clutch testing performed on the machine.Spin Coating Abrasive Clutch Test Machine plays an important role in the Clutch testing process for four-wheeled vehicles, but the situation in the field itself is not yet a system of care, especially in bearing parts which are the mechanical part of the Spin Coating Abrasive Clutch Test Machine. Mechanical Parts of Spin Coating Abrasive Clutch Test Machine using a system of rotation with the help of V-belt connected to the motor. Bearing problems can cause the performance of Spin Coating Abrasive Clutch Test Machine in Abrasive Clutch testing to affect the precision value of the test result, therefore an analysis is needed to calculate the lifetime of Bearing to prevent failure of test result. The research was conducted by observation in the field, direct interview with technician and operator, study literature until data analysis exist in the field.Keywords: Bearing Age (Lifetime) Bearing, Ball Bearing type UCF 4 Bolt Flange Unit, Spin Coating Abrasive Clutch Test Machine.ABSTRAKSpin Coating Abrasive Clutch Test Machine merupakan mesin untuk pengujian abrasive clucth pada kompononen kampas kopling (clutch) kendaraan roda empat PT.XY. Salah satu komponen yang berperan penting pada Spin Coating Abrasive Clutch Test Machine adalah bearing jenis Ball Bearing tipe UCF 4 Bolt Flange Unit. Permasalahan pada bearing dapat mengganggu kinerja dan hasil pengujian abrasive clutch yang dilakukan pada mesin tersebut.Spin Coating Abrasive Clutch Test Machine berperan cukup penting dalam proses pengujian Clutch untuk kendaraan roda empat, tetapi situasi di lapangan sendiri belum adanya suatu sistem perawatan terutama pada bagian bearing yang merupakan bagian mekanik fital dari Spin Coating Abrasive Clutch Test Machine. Bagian Mekanik dari Spin Coating Abrasive Clutch Test Machine menggunakan sistem Putaran dengan bantuan V-belt yang terhubung dengan motor. Permasalahan pada bagian Bearing dapat menyebabkan berkurangnya performa Spin Coating Abrasive Clutch Test Machine dalam pengujian Abrasive Clutch sehingga mempengaruhi nilai kepresisian dari hasil pengujian, maka dari itu diperlukannya suatu analisa untuk menghitung umur pakai ( lifetime) dari Bearing untuk melakukan pencegahan kegagalan hasil pengujian. Penelitian dilakukan dengan cara melakukan observasi di lapangan, wawancara langsung dengan teknisi dan operator, study literatur hingga analisa data yang ada di lapangan.Kata Kunci: Umur Pakai (Lifetime) Bearing, Ball Bearing tipe UCF 4 Bolt Flange Unit , Spin Coating